2022
DOI: 10.1039/d1fo02811a
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive investigation on the chemical diversity and efficacy of different parts of Ligusticum chuanxiong

Abstract: Ligusticum chuanxiong Hort. (CX) is a medicinal and edible plant with a wide range of constituents of biological interest. Since the biomass of the non-medicinal parts of CX is huge,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 25 publications
0
21
1
Order By: Relevance
“…Based on these data, we can correlate the results observed in present study with the chemical constituents identified in the extract. However, compared with previous studies ( Yan et al, 2022 ), CXL and CXR showed higher radical scavenging capacity. These differences can be attributed to differences in geography, harvest time, storage methods, and different extraction procedures and solvents.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…Based on these data, we can correlate the results observed in present study with the chemical constituents identified in the extract. However, compared with previous studies ( Yan et al, 2022 ), CXL and CXR showed higher radical scavenging capacity. These differences can be attributed to differences in geography, harvest time, storage methods, and different extraction procedures and solvents.…”
Section: Discussioncontrasting
confidence: 93%
“…In general, the aerial parts of plants are susceptible to biotic or abiotic stress, such as pests, herbivores, etc. Therefore, it is necessary to produce a higher level antioxidant metabolite for prevention, such as such as polyphenols and flavonoids ( Yan et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although leaves and petioles of A. sinensis are not traditionally used as medicinal parts, they are rich in coumarins and other compounds, such as falcarindiol (Zschocke et al., 1998). A recent report of the chemical diversity and efficacy of different parts of Ligusticum chuanxiong proposed the sustainable exploitation of the non‐medicinal organs of L. chuanxiong (Yan et al., 2022). As the non‐medicinal parts of A. sinensis possess a number of bioactive ingredients and abundant diversity of coumarins, we recommend a comprehensive investigation of the chemical diversity and efficacy of different parts of A. sinensis aiming for full exploitation of the previously underutilized leaves and petioles, alleviating resource waste and environmental pressure.…”
Section: Discussionmentioning
confidence: 99%
“…(CX), a medicine food homology plant of Umbelliferae, whose roots, Chuanxiong Rhizoma (CXR), is a traditional southeast Asian herb that is used clinically to treat chest pain, headache, irregular menstruation, etc. [ 1 , 2 ]. Chinese Pharmacopoeia (Ch.P.…”
Section: Introductionmentioning
confidence: 99%